2011
DOI: 10.1097/bpo.0b013e3182288ae3
|View full text |Cite
|
Sign up to set email alerts
|

Acetabulotrochanteric Distance in Slipped Capital Femoral Epiphysis

Abstract: Level IV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 12 publications
0
8
0
Order By: Relevance
“…Studies report a mean delay in the diagnosis of SCFE of about five to 10 months but extremes of up to three years from onset to diagnosis have also been reported [2][3][16][17][18][19][20]. A greater delay results in a slip of higher severity and worse long-term outcomes after treatment [2][3][7][8]12,14,[16][17][18][19][20][24][25]. Kocher found a significant relationship between a delay in diagnosis and slip severity (<30⁰: 10 weeks, 30⁰-50⁰: 14.4 weeks, >50⁰: 20.6 weeks) [17].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Studies report a mean delay in the diagnosis of SCFE of about five to 10 months but extremes of up to three years from onset to diagnosis have also been reported [2][3][16][17][18][19][20]. A greater delay results in a slip of higher severity and worse long-term outcomes after treatment [2][3][7][8]12,14,[16][17][18][19][20][24][25]. Kocher found a significant relationship between a delay in diagnosis and slip severity (<30⁰: 10 weeks, 30⁰-50⁰: 14.4 weeks, >50⁰: 20.6 weeks) [17].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, a greater than 2 mm sideto-side difference of the transection of the capital epiphysis by the Klein line increases the sensitivity of the AP pelvis view to detect an SCFE to 79% [27]. Song et al showed that the sensitivity of the AP pelvis view to diagnose a slip increases to 76% if the acetabulotrochanteric distance is greater than 2mm [19]. Bloomberg et al found that a wide, irregular physis is the most reliable sign of an early slip on the AP pelvis projection.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations